Pengembangan Sundial Horizontal Untuk Daerah Ekuator Tropis Selatan: Studi Kasus di Kota Surabaya Jawa Timur - Kahbi Zauri, Farhan (Azimuth: Journal of Islamic Astronomy, 2024)
This article aims to explain the process of constructing a horizontal sundial with criteria suitable for use in tropical latitudes or regions near the imaginary equator line, specifically in the Surabaya area; and to describe the results of measuring the sundial's criteria through testing based on the local digital time. This research is a type of R&D study using a qualitative approach. The techniques employed include observation, documentation, and experimentation. The primary data source used by the researcher is the gnomon’s shadow exposed to sunlight, while secondary data sources include books, scientific papers, latitude-longitude data, and websites containing information on horizontal sundials. The study found four minimum size measurements based on the technique of adapting the horizontal sundial to subtropical latitudes, with the smallest minimum diameter being 89.974 cm. By using this minimum precision standard, the horizontal sundial’s accuracy increases compared to using sundials with a diameter smaller than the stated size. The larger the horizontal sundial size in tropical latitudes, the greater the impact on its accuracy. Conversely, smaller horizontal sundials in tropical latitudes result in decreased accuracy, with the 89.974 cm diameter serving as a minimum reference for the Surabaya latitude.